DIRECTOR AND EXECUTIVE REMUNERATION CLAWBACKS: A SUGGESTED APPROACH FOR SOUTH AFRICA - Vela Madlela (Obiter, 2018)
The purpose of this article is to explore clawbacks as a means of addressing problematic executive remuneration through an examination of the approaches adopted by the US, Australia, and certain European Union (EU) member states and to highlight the lessons that South Africa may draw from the experiences of these jurisdictions. The article first considers the intentions and assumptions of remuneration reforms, which have introduced clawbacks in these international jurisdictions. It then moves on to provide an overview of the US, Australian and EU clawback reforms, identifying and analysing the potential benefits and shortcomings of the regulatory reforms in each jurisdiction. The article asserts that the absence of a requirement for the clawback of incentive-based remuneration in South Africa is not in the interests of companies and their stakeholders since shareholders will have to institute often protracted and costly legal proceedings in order to recover erroneously awarded incentives. The article then makes recommendations on how remuneration clawbacks could be effectively incorporated into the South African regulatory framework.